Angiomyxoma of thigh in a young lady: rare presentation - Singh L., Gopisingh; Sulthana, Reshmi; A. M., Adarsha; Ramavath, Krishna; B., Harikrishna (International Surgery Journal, 2023)
Angiomyxoma is a rare tumor that typically occurs in the perineum in women of reproductive age. It is very rare to present in the subcutaneous plane at thigh region in a young female. Angiomyxoma belongs to one group of myxomas tumors. They occur at various locations such as heart, bones, skin subcutaneous and aponeurotic tissues, urogenital tract and skeletal muscles. These tumors are characterized by having abundant mucoid and myxoid extracellular matrix. Angio myxoma is a rare benign mesenchymal tumor in approximately in 95% cases. The incidence is reported as varying from 0.1 to 0.13 per 100,000 population. These tumors are encompassing a broad spectrum of clinical behavior ranging from benign to malignant. Most of these tumors located in intramuscular plane and in our case the tumor located in the subcutaneous plane and presented in a young lady. We have done wide local excision for that tumor and came out as cutaneous angiomyxoma of thigh. We are concluding that due to these tumors having broad spectrum of clinical behavior as well as high rate of recurrence, preoperatively thoroughly investigated to rule out the soft tissue sarcomatous conditions as well as to plan exact mode of treatment.